EFFECTS OF GLYCYRRHIZIN PRE-TREATMENT ON TRANSIENT ISCHEMIC BRAIN INJURY IN MICE - Lim, Chiyeon; Lim, Sehyun; Lee, Young-Jun; Kong, Bokcheul; Lee, Byoungho; Kim, Chang- Hyun; Kim, Buyeo; Cho, Suin (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Ischemia-induced brain damage is the leading cause of adult disability and the fifth leading cause of death, and thus, the development of anti-apoptotic neuro-protective therapeutic agents is viewed as an attractive developmental strategy. Glycyrrhizin is the main sweet component in licorice and has a number of pharmacological activities, which include neuro-protective, anti-fungal, and anti-cariogenic activities. This study was undertaken to investigate the effects of glycyrrhizin on ischemia-induced brain damage. Materials and Methods: In infarct volumes and the levels of several apoptosis-related proteins, caspase-3, - 8, 9, Bcl-xL, Bcl-2,and their activities in the brains of middle cerebral artery occlusion (MCAO) treated mice were measured using western blotting methods. Results: Single pre-treatment with glycyrrhizin (10-100 mg/kg)at 2 hours before MCAO significantly reduced infarct volumes at 24h after MCAO. In addition, glycyrrhizin effectively inhibited the activations of caspase-3 and -9 and the down-regulation of Bcl-xLprotein caused by MCAO. Conclusion: The neuro-protective effect of glycyrrhizin was found to be due to its regulation of apoptosisrelated proteins signals.The authors suggest glycyrrhizin be considered a potential candidate for the treatment of ischemia induced brain damage.